In vitro inhibition of acetylcholinesterase and monoamine oxidase by Syzygium cumini leaves extract and preliminary assessment in animal models - Borba, Laryssa Alves [UNESP]; Wiltenburg, Victor Distefano; Negri, Giuseppina; Ibe, Mariana Bittencourt [UNESP]; Santos, Lucinéia dos [UNESP]; Mendes, Fúlvio Rieli (Elsevier, 2022)
Syzygium cumini (Myrtaceae) is a tropical tree used in traditional medicines to treat several diseases. All parts of S. cumini are used for medicinal purposes and present antioxidant potential. In this study, we evaluated the phytochemical composition of the ethanolic extract of S. cumini leaves (EESC) and its biological activity in vitro and in vivo regarding some effects on the central nervous system. Behavioral tests of anxiety, depression, and memory were performed with mice and the cerebral cortex used to evaluate lipoperoxidation and the acetylcholinesterase activity ex vivo. The EESC showed the presence of flavonoids, tannins, and gallic acid esters-4-O-glucurosides, detected for the first time in the species. The EESC presented antioxidant capacity in vitro with EC50 of 82.8 μg/mL in the DPPH assay and IC50 of 1.27 μg/mL in the lipoperoxidation test. The EESC inhibited the in vitro acetylcholinesterase and monoamine oxidase activities presenting IC50 of 44.54 and 432.7 μg/mL, respectively. However, the EESC did not show significant effects on the behavioral tests and ex vivo assays. Our results confirm the potential of EESC as a source of bioactive compounds acting on important target enzymes for central nervous system disorders, but the in vivo effects must be better evaluated.
Keywords: Acetylcholinesterase inhibition; Flavonoids glycosides; Hydrolysable tannins; Monoamine oxidase inhibition; Syzygium cumini